Analysis of Factors Affecting E-Loyalty With E-Trust and E-Satisfaction as Mediation Variables on Halodoc Application Users in Indonesia - Andrew Chandra; Pauline Henriette Pattyranie Tan (PT Mattawang Mediatama Solution, 2022)
This study aims to analyze: the influence of factors that affect e-loyalty with e-trust and e-satisfaction as mediating variables on Halodoc application users. Data collection was carried out using a questionnaire. The target population of the study is individuals aged > 17 years, who have done online teleconsultation at Halodoc at least 2 times and are willing to be respondents. Determination of the number of samples is determined by 280 samples. The sampling technique used was purposive sampling. The data was processed using Partial Least Square-Structural Equation modeling (PLS-SEM). The results show that the Technology Acceptance Model factors such as user interface quality, perceived security risk, and perceived privacy have a positive effect on e-trust and information quality, perceived security risk, perceived privacy, and e-commerce awareness have a positive effect on e-satisfaction, in This study found that information quality and e-commerce awareness do not have a positive effect on e-trust and user interface quality does not have a positive effect on e-satisfaction. Finally, e-trust has a positive effect on e-loyalty and e-satisfaction has a positive effect on e-loyalty for Halodoc application users in Indonesia. Managerial implications based on the results of data analysis, Halodoc must maintain the visual design of the application, display attractive information, the quality of the features contained in the application, update and provide up-to-date health information, maintain the security of patient's data and also providing 24-hour customer service, increasing awareness by increasing service promotions, providing public webinars or health talks, providing compensation to customers if there are problems regarding the services provided by Halodoc.